Penerapan teknik penguatan (Reinforcement) dalam Pendidikan Agama Islam: Perspektif Behavioristik - firjiyanti, riskita wulan (Maliki Interdisciplinary Journal, 2026)
Islamic Religious Education (PAI) in schools generally still relies on lecture-based teaching, which has been less effective in shaping students’ religious behavior. This is reflected in low levels of discipline, honesty, and social concern, indicating a gap between students’ understanding of religious material and their daily practice. This study analyzes the use of reinforcement based on Behaviorist theory as a strategy to improve positive behavior in PAI learning. The theories of Watson, Thorndike, and Skinner emphasize that behavior is formed through stimulus–response mechanisms, repetition, and consequences, which align with the concept of habituation in Islamic education. The analysis shows that PAI teachers have implemented both positive and negative reinforcement, but the application remains inconsistent, poorly planned, and dependent on personal experience. Challenges arise from limited understanding of the theory, inadequate facilities, and students’ dependence on material rewards. This study highlights that non-material reinforcement, moral acknowledgment, and continuous evaluation of behavioral progress are more effective in developing Islamic character. By applying reinforcement systematically and measurably, PAI learning can more effectively foster students’ religious behavior and moral conduct in the long term.